Consumer's cultured meat perception and acceptance determinants: a systematic review and future research agenda - Abd Hanan, Firdaus; Ab Karim, Shahrim; Ab Aziz, Yuhanis; Che Ishak, Farah Adibah; Sumarjan, Norzuwana (John Wiley and Sons Inc, 2024)
The reliance on animal husbandry for protein has caused environmental, social and ethical challenges worldwide, yet the demand for animal-based food continues to rise. Despite the increasing attention from scholars and professionals on the potential of cultured meat (CM) as a viable alternative protein source, the ensuing scholarly work still lacks coherence and is incomplete and fragmented. Its success also depends heavily on customer acceptance. This study therefore examined peer-reviewed literature on consumers' perceptions and acceptance of CM. A comprehensive search was conducted on ScienceDirect, Google Scholar and Scopus databases between 2017 and 2022, yielding 54 papers that met the selection criteria. The qualitative synthesis conducted revealed seven themes that had the highest influence on consumers' acceptance of CM. The themes identified were (i) attitudes and traits, (ii) situational impact, (iii) information and nomenclature, (iv) CM properties, (v) risk–benefit perception, (vi) familiarity and awareness and (vii) competition with other alternative proteins. This review also identified demographic predictors of consumers who are most likely to accept CM. The review found that although consumers are curious and willing to try CM, failure to address personal attitudes and traits may lead to failure in adoption. It was also found that strategies that include emotional responses are more effective in the long run.